PENEGAKAN HUKUM PEMERINTAHAN TERHADAP PELAKSANAAN HIBURAN MALAM DI KOTA PEKANBARU TAHUN 2022 (STUDI KASUS HIBURAN MALAM GOLD DRAGON) - Fikri, Zackiul; ', Isril (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In this research, there are several problematic phenomena raised in 2022 regarding Government Law Enforcement regarding the Implementation of Nightlife in Pekanbaru City in 2022 regarding the public's unrest regarding the